2015
DOI: 10.1093/occmed/kqv046
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of noise-induced hearing loss among Tanzanian miners

Abstract: BackgroundTanzania has a young mining history with several operating open pit and underground mines. No prevalence studies of noise-induced hearing loss (NIHL) have been conducted among mine workers to provide an impetus for the development of comprehensive hearing protection programmes.AimsTo determine the prevalence of NIHL and associated factors among miners in a major gold mining company operating in Tanzania. Associated risk factors such as age, sex and duration of exposure were examined.MethodsAudiograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 4 publications
1
24
0
17
Order By: Relevance
“…A significant improvement was observed in terms of noise-induced hearing loss among workers. We have observed a healthy population with an overall average proportion of NIHL of 12.9% (95% CI: 10.1-16.2), which is quite high for western standards but is significantly lower than previously reported cases in sub-Saharan Africa [9,10]. Safety at workplace appeared to be a term that has entered the common language and precautions are taken seriously against the hazards of loud noise.…”
Section: Study Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…A significant improvement was observed in terms of noise-induced hearing loss among workers. We have observed a healthy population with an overall average proportion of NIHL of 12.9% (95% CI: 10.1-16.2), which is quite high for western standards but is significantly lower than previously reported cases in sub-Saharan Africa [9,10]. Safety at workplace appeared to be a term that has entered the common language and precautions are taken seriously against the hazards of loud noise.…”
Section: Study Resultsmentioning
confidence: 48%
“…Both of these domains report alarming proportions of noise-induced hearing loss. Musiba et al [9] reported a proportion of NIHL as high as 47% within a population of Tanzanian miners. This is paired with a lack of hearing conservation programs (HCP) as reported by Moroe et al [11] Nigeria is a rapidly developing country with growing industries where occupational hazards are a widely unknown subject [11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When compared to the hearing loss prevalence of workers in other countries, the prevalence of respondents in this study showed a more severe condition as it was higher. Prevalence of hearing loss in other countries included 22% among New York farmers (Hwang et al 2001), 56.8% among Nigerian steel rolling mill workers (Ologe et al 2006), 44.2% among Brazilian metallurgical workers (Geovanna et al 2014) and 47.0% among Tanzanian miners (Musiba 2015).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The HCP is an action program that includes at least 7 elements but the current HCP program has only (i) monitoring, (ii) audiometric testing, (iii) hearing protection devices (HPD), (iv) employee training and education, and (v) record keeping. 1,2 However, an increase in the prevalence of NIHL was reported in various countries [3][4][5][6] and in Thailand. The percentage of Thai workers who reported NIHL 7 increased from 1.2% in 2000 to 4.7% in 2001.…”
Section: Introductionmentioning
confidence: 99%